I want to find Euler-Lagrange equation for the following:

$$J(u) = \int \left( \frac{\psi(x) u + \dot{u}}{\psi(x)u - \dot{u}} \right)dx, \text{where} \ \psi(x) \ \text{is an explicit function of} \ x.$$

First, I have made the following substitution:

$$y = \frac{\dot{u}}{u} \implies \int \left( \frac{\psi(x) u + \dot{u}}{\psi(x)u - \dot{u}} \right)dx = \int \left( \frac{\psi(x) + y}{\psi(x) - y} \right)dx$$

This substitution should reduce the Euler-Lagrange equation to a first-order differential equation.

I know that the Euler-Lagrange equation, in general, looks like this:

$$\frac{d}{dt}(f_{\dot{x}}) - f_x = 0$$

Should the Euler-Lagrange for this particular functional look like this:

$$f(\psi(x), y, x) = \frac{\psi(x) + y}{\psi(x) - y} \implies \frac{d}{dx}(f_{\psi(x)}) - f_y = 0$$

  • $\begingroup$ Is $\dot u = du/dx$? $\endgroup$ – David Nov 25 '14 at 1:10
  • $\begingroup$ Yes, $\dot u = du/dx$. $\endgroup$ – GaMbiTaaaa Nov 25 '14 at 1:25

According to my calculations, this is ugly:

$$\dfrac{\partial L}{\partial u}=\dfrac{-2 \psi \dot u}{(\psi u-\dot u)^2},$$ $$\dfrac{\partial L}{\partial \dot u}=\dfrac{2 \psi u}{(\psi u-\dot u)^2},$$

with $L=\dfrac{\psi u+\dot u}{\psi u-\dot u}$. Euler-Lagrange equation says:

$$\dfrac{d}{dx}\dfrac{\partial L}{\partial \dot u}-\dfrac{\partial L}{\partial u}=0,$$


$$\dfrac{d}{dx}\dfrac{\partial L}{\partial \dot u}=2\dfrac{-\psi u\dot u-\psi\dot u^2+2\psi u \ddot u-\psi u^2 \psi'-\psi^2 u \ddot u^2}{(\psi u-\dot u)^3}$$


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.